(untitled) (Bangladesh Journal of Botany, 2015)
Effect of concentrate organic manure (wellgrow grain and wellgrow soil) and NPK improved the growth and yield of wheat. Significant improvement in terms of growth parameters like plant height, tillers, dry matter production and productive tillers with application of 120 : 60 : 60 NPK + 300 kg wellgrow soil/ha and at par with application of 120 : 60 : 60 NPK + 300 kg wellgrow grain/ha, treatment receiving 100% NPK + 300 kg wellgrow soil/ha resulted maximum grain yield (4545 kg /ha). Treatment of 100% NPK + 300 kg wellgrow grain/ha maintained higher straw yield (5715 kg/ha) and test weight (44.10 g) due to application of 100 % NPK along with 200 kg wellgrow soil/ha whereas it was at par with application of 75 and 100% NPK with both levels of wellgrow formulation. DOI: http://dx.doi.org/10.3329/bjb.v44i1.22738 Bangladesh J. Bot. 44(1): 143-146, 2015 (March)